The Influence Of Effort Expectancy, Social Influence, Payment Ability, Hedonic Motivation, Habit, Price Value, Customization And Advancement Towards Purchase Intention Of Virtual Items In The Game Player Unknown Battle Grounds Mobile - Grace Angel Leonardy (iBuss Management, 2021)
The rise of technology has made it possible for people to connect with each  other in so many different ways, virtual game world is one of them. This has also  created new phenomenon within the consumer behavior context and studies found that 1.1 billion has been spent by Indonesian gamers to buy virtual  items in online games. Added to the fact that now, games like PUBGM and Mobile  Legend offer mostly non-functional items, which are items that don’t enhance game  progression. The purpose of this research is to know what actually drives people that involves them exchanging real money to buy something intangible and even non-functional to their online characters. In particular, the researcher wants to know the influence effort expectancy, social  influence, payment ability, hedonic motivation, habit, price value, customization  and advancement towards purchase intention of virtual items in the game PUBGM.  The researcher collected 115 valid research data then analyzed using  multiple linear regression. It concluded that effort  expectancy, social influence, payment ability, hedonic motivation, habit, price  value, customization and advancement do affect purchase intention. Moreover, customization, advancement, and social influence act as the  biggest driver of purchase intention to buy non-functional virtual items in  PUBGM. Keywords: Effort Expectancy, Social Influence, Payment Ability, Hedonic Motivation, Habit, Price Value, Customization and Advancement Perceived Enjoyment, Purchase Intention, Virtual Items